INFLUENCE OF PHYSICAL RESOURCE MANAGEMENT ON ACADEMIC PERFORMANCE OF TRAINEES IN PUBLIC PRIMARY TEACHER TRAINING COLLEGES IN KENYA - Wagithunu, Margaret Nyambura; Edabu, Dr. Paul; Sinan, Dr. Ganatusanga Haroon (African Journal of Education and Practice, 2019)
Purpose: Importance of physical resource management on academic performance of teacher-trainees in teacher training colleges cannot be over-emphasized. However, academic performance of teacher-trainees has been dismal and continues to be on a downward trend. The purpose of this study was to investigate the influence of physical resource management on academic performance of trainees in public PTTCs in Kenya. Methodology: The target population was 22, 279 respondents comprising of 25 principals, 25 Deans of Curriculum, 1389 tutors and 20, 840 trainees. A sample of 372 respondents was calculated using Yamane's Formula. This comprised of eight principals, eight deans of curriculum, 160 tutors and 196 teacher-trainees. Questionnaires were used to collect data from tutors and trainees whereas interview guides were used to gather information from principals and deans of curriculum. The study was guided by the human capital theory. Qualitative data were analyzed thematically along the objectives and presented in narrative forms. Quantitative data was analyzed descriptively and inferentially using linear regression using Statistical Packages for Social Science (SPSS Version 23) and presented using tables and charts. Findings: The findings confirmed that the availability and management of physical facilities such as libraries and lecture halls are core in attaining the educational objectives. This implies that the poor condition of college facilities brings about critical concerns on college tutors' and trainees' general welfare. The study established that physical resource management do effectively influence teacher trainees' academic performance in public TTCs in Kenya. Unique contribution to theory, practice and policy: The study findings conclude that curriculum implementers need to be aware of the phenomena of mismanagement of physical resources in public PTTCs as it leads to straining of the tutors, overstretching the available resources and substandard training of students. The study recommends that there is need to supply colleges with adequate resources, ensure effective utilization of resources and ensure proper maintenance of resource through supervision by teachers' service commission.